Cultivar differences in carbon and nitrogen accumulation, balance, and grain yield in maize - Li, Qiang; Ren, Yun; Fu, Hao; Li, Zhexin; Kong, Fanlei; Yuan, Jichao (Frontiers in Plant Science, 2022)
Using the N-efficient cultivar Zhenghong 311 (ZH 311) and the N-inefficient cultivar Xianyu 508 (XY 508) as research sources, the differences in C and N accumulation and balance in maize cultivars with contrasting N efficiencies were compared to analyze the correlation between the accumulation and balance of C and N with grain yield. According to the results, the ZH 311 cultivar had higher C and N accumulation in each stage and grain yield than the XY 508 cultivar, while the C/N ratio in each stage and organ was significantly lower in ZH 311 than in XY 508, with the greatest difference occurring in the silking stage and leaf, indicating that the N-efficient cultivar ZH 311 had evident advantages in accumulation and balance of C and N and grain yield than the N-inefficient cultivar XY 508. Moreover, the C and N accumulation and grain yield increased significantly with N application, while the C/N ratio in each stage and organ decreased significantly with N application, but the differences between ZH 311 and XY 508 increased first and then decreased with the increase of N level, indicating that the accumulation and balance of C and N, as well as the grain yield advantage of N-efficient cultivar ZH 311 over N-inefficient cultivar XY 508, were higher under low and medium N levels, while high N application was more conducive to the N-inefficient cultivar XY 508 and improved the accumulation and balance of C and N, and grain yield. Furthermore, grain yield was positively correlated with C and N accumulation, affected by pre-anthesis N and post-anthesis C accumulation, and negatively correlated with the C/N ratio, with the highest correlation between grain yield and the C/N ratio in silking stage and leaf. In conclusion, the N-efficient cultivar could better coordinate the C and N balance of the plant, especially the C and N balance in the silking stage and leaf, promote photosynthetic product storage and transport, prolong the leaf function period, and make the pre-anthesis and post-anthesis C and N accumulation of ZH 311 significantly higher than those of XY 508, allowing higher grain yields.